Lipid Driven Nanodomains in Giant Lipid Vesicles are Fluid and Disordered - Alena Koukalová (Nature Portfolio, 2017)
Abstract It is a fundamental question in cell biology and biophysics whether sphingomyelin (SM)- and cholesterol (Chol)- driven nanodomains exist in living cells and in model membranes. Biophysical studies on model membranes revealed SM and Chol driven micrometer-sized liquid-ordered domains. Although the existence of such microdomains has not been proven for the plasma membrane, such lipid mixtures have been often used as a model system for ‘rafts’. On the other hand, recent super resolution and single molecule results indicate that the plasma membrane might organize into nanocompartments. However, due to the limited resolution of those techniques their unambiguous characterization is still missing. In this work, a novel combination of Förster resonance energy transfer and Monte Carlo simulations (MC-FRET) identifies directly 10 nm large nanodomains in liquid-disordered model membranes composed of lipid mixtures containing SM and Chol. Combining MC-FRET with solid-state wide-line and high resolution magic angle spinning NMR as well as with fluorescence correlation spectroscopy we demonstrate that these nanodomains containing hundreds of lipid molecules are fluid and disordered. In terms of their size, fluidity, order and lifetime these nanodomains may represent a relevant model system for cellular membranes and are closely related to nanocompartments suggested to exist in cellular membranes.